THE RELATIONSHIP KNOWLEDGE AND ATTITUDE OF MOTHERS WHO HAVE BABIES 0-6 MONTHS TO GIVING MP ASI IN NAGORI PITU MARIHAT ISLAND UJUNG SUB-DISTRICT SIMALUNGUN REGENCY - Shofian Syarifuddin; Mustaruddin; Wilson Samosir (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Complementary Food for Mother's Milk (MP-ASI) is additional food besides breast milk which is given to babies after the baby is 6 months old. In addition to solids, breast milk must still be given to babies, at least until 24 months. The cause of the disturbance in the growth and development of the baby is due to the administration of MP-ASI by the mother who is not in accordance with the timeliness of administration, frequency, type, amount of food ingredients, and the method of preparation. in infants in Nagori, Pitu Marihat Island, Ujung Padang District, Simalungun Regency. This type of research is an analytic survey using cross sectional, The population in the study were all mothers who had babies aged 0-6 months, namely 60 babies and were used as the total sample. Data were obtained by interview using a questionnaire and analyzed by the chi-square test. From the results of the chi-square test (a <0.05), it shows that there is a significant relationship between knowledge and giving MP-ASI to infants, obtained p = 0.002. And there is a significant relationship between mother's attitude and the accuracy of giving MP-ASI to babies. p-value = 0.029. It is hoped that the health workers who work at the Puskesmas in Nagori Pulau Pitu, Ujung Padang will more routinely conduct counseling about proper MP-ASI to mothers personally.